2008
DOI: 10.1097/qad.0b013e328304b38b
|View full text |Cite
|
Sign up to set email alerts
|

Rates of hospitalizations and associated diagnoses in a large multisite cohort of HIV patients in the United States, 1994–2005

Abstract: The rates of hospitalizations for HIV-infected patients declined substantially during 1994-2005, due mainly to reductions in the AIDS opportunistic infections. Compared with the period 1994-1997, patients in the highly active antiretroviral therapy era were hospitalized with higher CD4+ cell counts and more frequently for chronic end-organ conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
109
3
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(137 citation statements)
references
References 38 publications
13
109
3
8
Order By: Relevance
“…Longitudinal studies have shown downward trends in both hospitalizations and emergency department (ED) visits after initiation of ART. [3][4][5] Gains in health, longevity, and reductions in acute care usage, however, have not been uniform across all population groups in the US. Among HIV-infected individuals, women, 6-9 injection drug users, 7,8,10 and racial/ethnic minorities 8,11,12 account disproportionately for morbidity and suboptimal health-care utilization patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies have shown downward trends in both hospitalizations and emergency department (ED) visits after initiation of ART. [3][4][5] Gains in health, longevity, and reductions in acute care usage, however, have not been uniform across all population groups in the US. Among HIV-infected individuals, women, 6-9 injection drug users, 7,8,10 and racial/ethnic minorities 8,11,12 account disproportionately for morbidity and suboptimal health-care utilization patterns.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] With the introduction of highly active antiretroviral therapy (HAART) in 1996, overall rates of hospitalization among HIV-infected patients declined significantly, particularly for AIDS-related issues, 9 though subsequently admissions for other causes (liver disease, non-opportunistic infections) increased 1,2,4 and demonstrated ongoing health disparities for women, 1 patients with serious mental illness, 10 injection drug users 7,10 and African Americans. 1,5,8,11 In the HAART era, national HIV hospitalization costs were 3.2 billion in 2005, 12 and costs for readmissions in this population may be up to 32% higher than the index admission.…”
mentioning
confidence: 99%
“…In fact, HIV patients, along with trauma, burn, and oncology patients, have traditionally been excluded from preventable readmission analyses, 28 due ''to the complexity of the patient and the low likelihood that a readmission can be prevented''. 29 Though HIV can be readily treated as an outpatient with excellent outcomes, admission and readmission rates remain high, especially among disadvantaged populations, 9 suggesting that many readmissions among HIV patients are potentially preventable. In addition, inpatient admissions among HIV patients represent a unique opportunity to improve clinical outcomes, including a reduction in hospital admissions, through engagement in routine HIV care, treatment with antiretroviral therapy, and eventual virologic suppression.…”
mentioning
confidence: 99%
“…Therefore, the focus of HIV/AIDS care has been shifting from inpatient medical treatment to outpatient-based chronic disease management. However, the hospitalization rate and inpatient mortality rate remained higher in PLWH despite increasing accessibility to HAART in comparison to either the general population or HIV-negative individuals (4)(5)(6).…”
Section: Introductionmentioning
confidence: 94%